2022
DOI: 10.3897/phytokeys.192.79702
|View full text |Cite
|
Sign up to set email alerts
|

Flora of Mongolia: annotated checklist of native vascular plants

Abstract: In this study, we critically revised and updated the checklist of native vascular plants of Mongolia. The checklist comprises 3,041 native vascular plant taxa (2,835 species and 206 infraspecific species) from 653 genera and 111 families, including 7 lycophytes, 41 ferns, 21 gymnosperms, and 2,972 angiosperms. In the angiosperms, we identified the 14 families with the greatest species richness, ranging from 50 to 456 taxa. Species endemism is also noted here; 102 taxa are endemic to Mongolia, and 275 taxa are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 44 publications
(57 citation statements)
references
References 98 publications
0
52
0
5
Order By: Relevance
“…CS: VU (2)] (Figure 3) Acanthophyllum pungens is distributed in China (Xinjiang), Iran, Kazakhstan, Kyrgyzstan, Mongolia, Turkeminstan, and Uzbekistan (Ghaff ari, 2021). In Mongolia, A. pungens is distributed in three regions namely, Mongolian Altai, Dzungarian Gobi and Khovd regions (Baasanmunkh et al, 2022a), but we did not found any herbarium specimens from the Khovd region. 2021a).…”
mentioning
confidence: 62%
See 4 more Smart Citations
“…CS: VU (2)] (Figure 3) Acanthophyllum pungens is distributed in China (Xinjiang), Iran, Kazakhstan, Kyrgyzstan, Mongolia, Turkeminstan, and Uzbekistan (Ghaff ari, 2021). In Mongolia, A. pungens is distributed in three regions namely, Mongolian Altai, Dzungarian Gobi and Khovd regions (Baasanmunkh et al, 2022a), but we did not found any herbarium specimens from the Khovd region. 2021a).…”
mentioning
confidence: 62%
“…Mongolia's South Gobi region, according to Baasanmunkh et al (2022a). In addition, we found it in the Trans-Altai Gobi region based on herbarium collection (NS0026300).…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations